Emergence of Visible‐Light Water Oxidation Upon Hexaniobate‐Ligand Entrapment of Quantum‐Confined Copper‐Oxide Cores. Issue 10 (25th January 2023) - Kumar Tiwari, Chandan; Roy, Shubasis; Tubul‐Sterin, Tal; Baranov, Mark; Leffler, Nitai; Li, Mu; Yin, Panchao; Neyman, Alevtina; Weinstock, Ira A.
Abstract: The formation of small 1 to 3 nm organic‐ligand free metal‐oxide nanocrystals (NCs) is essential to utilization of their attractive size‐dependent properties in electronic devices and catalysis. We now report that hexaniobate cluster‐anions, [Nb6 O19 ] 8−, can arrest the growth of metal‐oxide NCs and stabilize them as water‐soluble complexes. This is exemplified by formation of hexaniobate‐complexed 2.4‐nm monoclinic‐phase CuO NCs (1 ), whose ca. 350 Cu‐atom cores feature quantum‐confinement effects that impart an unprecedented ability to catalyze visible‐light water oxidation with no added photosensitizers or applied potentials, and at rates exceeding those of hematite NCs. The findings point to polyoxoniobate‐ligand entrapment as a potentially general method for harnessing the size‐dependent properties of very small semiconductor NCs as the cores of versatile, entirely‐inorganic complexes. Abstract : An example of sensitizer‐free visible‐light water oxidation by CuO was achieved using water‐soluble hexaniobate cluster anions to entrap quantum‐confined nanocrystals of the familiar earth‐abundant metal oxide.